Evaluation of a percutaneous bone conduction system using the Ponto BHX implant in a pediatric population with congenital conductive hearing loss—a 1 year prospective follow-up study - Josefsson Dahlgren, Hanna; Iversen, Kia Nøhr; Hultcrantz, Malou; Engmér Berglin, Cecilia (Frontiers in Audiology and Otology, 2025)
IntroductionBone conduction hearing systems is a well-established treatment for patients with conductive or mixed hearing losses, such as conductive hearing loss caused by congenital aural atresia. Percutaneous bone conduction systems consist of a titanium fixture implanted in a temporal bone and a skin penetrating abutment connecting to an external sound processor. Implant design and surgical techniques have developed over time and while one-stage minimally invasive procedures have long been the standard in adult patients, the development has been more cautious in pediatric patients as they have been more prone to complications and implant loss. The purpose of this study was to collect systematic data from a pediatric population receiving a percutaneous bone conduction hearing device, the laser ablated Ponto BHX implant, in a one-stage surgical procedure.MethodsProspective, one-armed, observational cohort study of children undergoing surgery for a percutaneous bone conduction device with a laser ablated fixture. Outcomes were assessed at screening, during surgery, 7–10 days after surgery, 6–14 weeks after surgery, and 12 months after surgery. The primary outcome was implant stability over 12 months. Furthermore, implant survival, skin reactions, and audiological performance were evaluated, and implant survival was compared to a retrospective control cohort.ResultsFifteen study participants with a mean age of 6 years (range 3–12 years) were included. Three were bilaterally implanted, rendering a total of 18 implants. Implant stability showed a 10-point increase in mean implant stability measurements at 12 months, compared to at surgery. Four implants (22%) were lost before the 12-month follow-up, which was comparable to the retrospective cohort where the 12-month implant loss rate was 23%. Across the 12-month period, 8/18 implant sites had a maximum Holgers score of 0, indicating no skin reactions. The remaining implant sites had a maximum Holgers score of 1–3.ConclusionIn conclusion, this study shows safe and reliable outcomes using laser ablated fixtures for one stage surgery in a pediatric population.Public trial registrationClinicalTrials.gov, identifier: NCT03723161.